Evaluation of legal periodical collections of selected law school libraries in Metro Manila - Echiverri, Lilia Fonbuena 1951- (1996)
The general evaluation of the legal periodical collection of UPCL is rated outstanding (4.12 - 4.21) in supporting the law school program and research needs of students and faculty. The ADMUSL rated their overall program very sufficient (3.12 - 3.85). SBCLL legal periodical collection all sufficient (2.19 - 2.54) in supporting the overall programs and objectives of the college, adequacy in supporting the professional program and research needs. USTFCL also rated their law library as satisfactory (2.37 - 2.54)
The objectives of this study are to evaluate the legal periodical collections in relation to up-to-dateness, growth rate, strengths and weaknesses of the legal periodical collections as perceived by faculty members and law students; and to produce a standard list of legal periodical titles that will serve as basis for the establishment of a standard periodicals collection. This study covers the legal periodical collections of the University of the Philippines College of Law Library (UPCL), Ateneo de Manila University Law School Library (ADMULSL), San Beda College of Law Library (SBCLL) and University of Santo Tomas Faculty of Civil Law Library (USTFCL). The faculty members and law students were the respondents. They were chosen by means of purposive random sampling. The faculty and students assessed the adequacy of the law library legal periodical collections utilizing a combination of impressionistic, qualitative and quantitative methods. The evaluation of the legal periodical collections of the four law school libraries revealed that UPCLL legal periodical collection is outstanding. The faculty and students from ADMULS evaluated their legal periodical collections on law as sufficient. SBCL and USTFCL evaluated their collection as barely sufficient. UPCL and ADMULS have very current or very up-to-date collections. SBCL and USTFCL collections are up-to-date. The UPCLL has a growth rate of 13.92 percent and ADMULSL has 2,66 percent growth rate. The legal periodical collection of UPCL is outstanding with 431 titles followed by ADMULSL with 301 titles. SBCLL and USTFCLL are not sufficient enough to meet the needs of their respective users since they have only 38 titles each which fall below standards. UPCL rated very strong in one subject area. The other subject areas were rated as strong except for two subjects which were found to be weak. ADMULS were rated strong and weak while SBCL and USTCFL were rated as all weak.
Thesis (M.L.S.)--University of the Philippines, Diliman.
Typescript.
Vita.
Keywords: Law libraries -- Evaluation. -- Philippines -- Manila Metropolitan Area -- Periodicals